2012
DOI: 10.7740/kjcs.2012.57.3.219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seed Size Variation on Germination and Seeding Vigour of Sorghum (Sorghum bicolor L.)

Abstract: Seed size has been considered as an effective criteria for selection of the most vigorous seeds in sorghum [(Sorghum bicolor (L) Moench]. The smaller seeds were inferior to the larger sizes in emergence and grain yield. This study was conducted to determine germination rate, field emergence and vigor of sorghum for selection of high quality seed by different seed size. Sorghum cultivar of two (Hwanggeumchal and Tojong) were separated into five seed size proportion (<2.36, 2.80, 3.15, 3.35 and >3.55 mm diam.) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…In the present study, high inter-accession variation was observed in the germination pattern of seed from various population of S. bicolor. Our results agree with the studies of Jung et al [ 60 ], who showed a wide variation range (67–92%) in the germination percentage of Korean cultivars. Substantial variation in the germination rate of sorghum was also reported by Harris et al [ 61 ], who observed a close association between seed size and seed germination rate in sorghum.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, high inter-accession variation was observed in the germination pattern of seed from various population of S. bicolor. Our results agree with the studies of Jung et al [ 60 ], who showed a wide variation range (67–92%) in the germination percentage of Korean cultivars. Substantial variation in the germination rate of sorghum was also reported by Harris et al [ 61 ], who observed a close association between seed size and seed germination rate in sorghum.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, it is possible that the races may not show any definite relationship with levels of shoot fly resistance. Seed size influences germination and seedling vigor 52 . SH being related to seed size, it is possible that races having higher seed size and better vigor and seedling growth may have some influence in quickly escaping the sensitive stage as compared to races with lesser seed size.…”
Section: Discussionmentioning
confidence: 99%
“…Seed size influences germination and seedling vigor. 52 SH being related to seed size, it is possible that races having higher seed size and better vigor and seedling growth may have some influence in quickly escaping the sensitive stage as compared to races with lesser seed size. This relation, however, needs to be validated.…”
Section: Discussionmentioning
confidence: 99%